321 Phase I clinical trial assessing the combination of systemic chemokine modulatory regimen targeting TLR3 with neoadjuvant chemotherapy in triple negative breast cancer. (9th November 2020) - Gandhi, Shipra; Opyrchal, Mateusz; Ford, Cayla; Fitzpatrick, Victoria; Grimm, Melissa; Basse, Per; Quinn, Marie; Witkiewicz, Agnieszka; Attwood, Kristopher; Ernstoff, Marc; O'Connor, Tracey; Early, Amy; et al.
Abstract : Background: Neoadjuvant chemotherapy (NAC) with taxanes is the standard of care in triple negative breast cancer (TNBC). Intratumoral prevalence of CD8+ cytotoxic T-lymphocytes (CTLs) is associated with an improvement in relapse-free survival (RFS) and overall survival (OS), while regulatory T-cells (Treg) and myeloid derived suppressor cells (MDSC) are associated with poor survival. Higher ratio of CTL/Treg is associated with higher probability of obtaining pathological complete response (pCR), a surrogate marker for RFS. Intratumoral production of CCL5, CXCL9, CXCL10 and CXCL11 is critical for local infiltration with CTLs, while CCL22 is responsible for Treg attraction. Previous studies have shown that CXCL9 expression in the pre-treatment breast tissue is associated with a three-fold higher rate of achieving pCR. Our preclinical data show that Chemokine modulating (CKM) regimen, combining rintatolimod (TLR3 agonist), interferon (IFN)-α2b, and celecoxib (COX-2 inhibitor) increases CTL-attracting, and decreases MDSC-, Treg-favoring chemokines, increasing CTL/Treg ratio in tumor microenvironment, with preferential tumor tissue activation than adjacent healthy tissues. We hypothesize that the combination of CKM with paclitaxel will result in infiltration of TNBC with CTLs, and along with doxorubicin/cyclophosphamide (AC), result in higher pCR, translating into improved RFS and OS. Methods: In this phase I study NCT04081389, eligibility includes age ≥18 years, confirmed resectable TNBC, radiographically measurable disease ≥1 cm, ECOG PS ≤ 2, adequate organ and marrow function. Patients with autoimmune disease, serious mood disorders, invasive carcinoma within 3 years, history of peptic ulcers or hypersensitivity to NSAIDs will be excluded. We plan to treat three patients with early stage TNBC with paclitaxel 80 mg/m2 IV weekly for 12 weeks, rintatolimod 200 mg IV, celecoxib 200 mg oral twice daily, and accelerated titration of IFN-α2b at doses 0, 5, or 10 million units (MU)/m2 [Dose Levels (DL) 1, 2 and 3 respectively] on days 1–3 (no intra-patient dose escalation) in weeks 1–3. Dose-limiting toxicity (DLT) is defined as grade 3 or higher toxicities within the first 3 weeks. Any DLT will mandate recruitment per the 3+3 model. If no DLT, three patients will be enrolled at DL 4 at 20 MU/m2 IFN- α2b. This will be followed by standard dose-dense AC, and then surgery. The primary endpoint is safety and tolerability of combination and to identify the appropriate DL of CKM and paclitaxel for extended efficacy study. The secondary endpoints include investigation of efficacy (pCR and breast MRI response), along with RFS and OS. Intratumoral biomarkers will be analyzed in an exploratory manner. Results: N/A Conclusions: N/A Trial Registration: NCT04081389 Ethics Approval: The study was approved by Roswell Park Comprehensive Cancer Center Institution's Ethics Board, approval number I-73718.